METODE PENDIDIKAN AGAMA ISLAM MENURUT IBNU KHALDUN DALAM BUKU MUKADDIMAH IBNU KHALDUN - Komalasari, Novi; Pasya, Rayi; Rohman, Ahmad Abdur (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2015)
This study aims to find out ways or methods of Islamic religious education according to Ibn Khaldun. After analyzing the data obtained results are: 1) From the formulation of Islamic religious education to be achieved Ibn Khaldun adheres to the principle of balance. Therefore, the purpose of education is to be achieved Ibn Khaldun clearly visible hallmark of religious education and moral religious breath. 2) Method of Islamic religious education that Ibn Khaldun is as follows: (a) method of staging and repetition, (b) use certain means to translate the lessons, (c) excursions is a tool to gain experience directly, (d) Not giving presentations complicated to children who are just learning the beginning, (e) Must be of relevance in the discipline, (f) Not to confuse the two science at a time, (g) It should not teach the Al-Quran to children except as to the extent of thinking abilities particular, (h) sanctions against the students is one of the motivations encouragement of learning.